Lack of correlation between outcomes of membrane repair assay and correction of dystrophic changes in experimental therapeutic strategy in dysferlinopathy. - William Lostal (Public Library of Science (PLoS), 2012)
Mutations in the dysferlin gene are the cause of Limb-girdle Muscular Dystrophy type 2B and Miyoshi Myopathy. The dysferlin protein has been implicated in sarcolemmal resealing, leading to the idea that the pathophysiology of dysferlin deficiencies is due to a deficit in membrane repair. Here, we show using two different approaches that fulfilling membrane repair as asseyed by laser wounding assay is not sufficient for alleviating the dysferlin deficient pathology. First, we generated a transgenic mouse overexpressing myoferlin to test the hypothesis that myoferlin, which is homologous to dysferlin, can compensate for the absence of dysferlin. The myoferlin overexpressors show no skeletal muscle abnormalities, and crossing them with a dysferlin-deficient model rescues the membrane fusion defect present in dysferlin-deficient mice in vitro. However, myoferlin overexpression does not correct muscle histology in vivo. Second, we report that AAV-mediated transfer of a minidysferlin, previously shown to correct the membrane repair deficit in vitro, also fails to improve muscle histology. Furthermore, neither myoferlin nor the minidysferlin prevented myofiber degeneration following eccentric exercise. Our data suggest that the pathogenicity of dysferlin deficiency is not solely related to impairment in sarcolemmal repair and highlight the care needed in selecting assays to assess potential therapies for dysferlinopathies.